Energy consumption modeling within the virtual commissioning tool chain - Hauf, D.; Meike, D.; Paryanto, Paryanto; Franke, Jörg (IEEE International Conference on Automation Science and Engineering, 2015)
In this paper an energy modeling approach within the virtual commissioning tool chain is presented. Virtual commissioning (VCom) today is a de facto methodology for programmable logic controller (PLC) software design and validation for automatic production systems. Energy consumption has never been an optimization criterion in VCom. Concepts of energy consumption modeling for any production unit have been investigated for measuring, visualization and optimization of control strategies. The hardware-in-the-loop simulation includes logical behavior models, the respective energy models and 3D-kinematic models of the production units, which are connected over common industrial bus network with a hardware-PLC. The concept has been developed for use with commercially available software tools so that the research results are implementation-oriented. An example from the automotive industry has been used.
CRIS-Team Scopus Importer:2023-03-07